Kicking foot swing planes and support leg kinematics in rugby place kicking: Differences between accurate and inaccurate kickers. Issue 4 (21st April 2019) - Bezodis, Neil E.; Atack, Alexandra; Willmott, Alexander P.; Callard, Jon E. B.; Trewartha, Grant
Abstract: Place kicking is a complex whole-body movement that contributes 45% of the points scored in international Rugby Union. This study compared the kicking foot swing plane characteristics of accurate and inaccurate kickers, underpinned by differences in their support leg and pelvis kinematics at support foot contact, to identify key technique characteristics. Motion capture data (240 Hz) were collected from 33 experienced kickers, and distinct groups of accurate ( n = 18) and inaccurate ( n = 8) kickers were identified based on their performance characteristics. All accurate kickers were capable of kicking successfully from at least 33.3 m, whereas all inaccurate kickers would have missed left from distances greater than 30.7 m. The accurate group exhibited a moderately shallower swing plane inclination (50.6 ± 4.8° vs. 54.3 ± 2.1°) and directed the plane moderately further to the right of the target (20.2 ± 5.4° vs. 16.7 ± 4.1°). At support foot contact, the accurate group placed their support foot moderately less far behind the ball (0.08 ± 0.08 m vs. 0.12 ± 0.04 m) and positioned their centre of mass moderately further to the support leg side (0.77 ± 0.07 m vs. 0.72 ± 0.01 m) due to a moderately greater stance leg lean (29.3 ± 4.1° vs. 26.8 ± 3.2°). The kicking foot swing plane is highly planar in rugby place kicking but its orientation differs between accurate and inaccurate kickers. These plane characteristics may be controlled by support foot placement and support leg and pelvis kinematics at support foot contact.